2008
DOI: 10.1259/dmfr/26038913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient light and monitor brightness and contrast settings on the detection of approximal caries in digital radiographs: anin vitrostudy

Abstract: Reducing ambient light to less than 50 lux significantly increased the accuracy of diagnosing approximal carious lesions on a monitor with an optimal brightness setting and an optimal or slightly higher than optimal contrast setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 13 publications
4
40
1
1
Order By: Relevance
“…This type of monitor is commonly used in dental practices. Before evaluation, monitor brightness and contrast 8 were adjusted visually using AAPM test images task group 18 (TG18)-QC and TG18-CT. 11 AAPM test images TG18-LN12-01, -09, and -18 11 were used to ensure that monitor luminance was unchanged for all evaluations. 3 sets of lighting conditions with varying illuminance at the monitor surface were evaluated: (a) ambient room light at 1000 lx (range, 1012-1057 lx); (b) 50 lx (range, 42-50 lx)-no hood was used on the monitor; and (c) bright light in the room and a hood mounted on the monitor.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This type of monitor is commonly used in dental practices. Before evaluation, monitor brightness and contrast 8 were adjusted visually using AAPM test images task group 18 (TG18)-QC and TG18-CT. 11 AAPM test images TG18-LN12-01, -09, and -18 11 were used to ensure that monitor luminance was unchanged for all evaluations. 3 sets of lighting conditions with varying illuminance at the monitor surface were evaluated: (a) ambient room light at 1000 lx (range, 1012-1057 lx); (b) 50 lx (range, 42-50 lx)-no hood was used on the monitor; and (c) bright light in the room and a hood mounted on the monitor.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies in recent years 3,8,9 have concluded that it is essential to optimize observation conditions for reading digital radiographs on a display monitor. Ambient light level in the room is a vital factor for optimizing diagnostic accuracy.…”
Section: Caries Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the outcome of this radiographic evaluation is not only depending on exposure parameters but also on image sensor type and viewing conditions [4][5][6][7][8][9][10][11][12][13][14]. Accuracy of alveolar bone level measurements on conventional or digital radiographs has been found to lie within 1 to 2 mm deviation [15][16][17], the latter resulting in similar [17][18][19] or greater accuracy [20][21][22].…”
Section: Introductionmentioning
confidence: 99%